Sāk vitt ok vītt of verǫld hverja - Koutsomichalis, Marinos (My University, 2026)
'Sāk vitt ok vītt of verǫld hverja' multimedia performance at Sparkling Sound Festival, Dansekapellet: https://dansekapellet.kk.dk/en/node/3343